PENILAIAN KESEHATAN KEUANGAN PADA KOSPIN JASA SYARIAH PEKALONGAN SEBAGAI LEMBAGA KEUANGAN MIKRO SYARIAH - Rinda Asytuti (IAIN Pekalongan, 2011)
Supervision of Islamic micro-finance institutions (LKMS), are necessary as control financing over the financial institution, whether it was healthy or not. Financial assessment was conducted by the agency to audit the financial system with the services of independent auditors, as stipulated in the Minister of Cooperatives and Small-Medium Enterprises, Nomor 14/Per/M.KUKM/XII/2009. The problem, though the provision of health assessment auditions financial institutions have been regulated, but LKMS, such as KJSP allegedly have not standard of operating procedures yet, to achieve the standards set out in the ministerial regulation. Nevertheless of standard, the study was aimed to assess the financial health of KJSP. The approach used in this study was quantitative, relying on the primary data, gathered from KJSPâ€™s Financial Report during 2004 - 2009 and interviews with managers KJSP. The results showed that KJSPâ€™s assets are 66,503 billion in 2009 and categorized as â€œHealthâ€ for all the ratios were calculated and â€œwell enoughâ€ to capital ratio. Nevertheless, the study faced organizational constraint of KJSP that limited the assessment of study. The â€œxâ€ factor of constraint assessment was related to the existence of KJSP was as a small part of â€”bigger unitâ€” Kospin JASA that still using conventional finance services.